2013
DOI: 10.1523/jneurosci.3429-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Modality-Based Organization of Ascending Somatosensory Axons in the Direct Dorsal Column Pathway

Abstract: The long-standing doctrine regarding the functional organization of the direct dorsal column (DDC) pathway is the "somatotopic map" model, which suggests that somatosensory afferents are primarily organized by receptive field instead of modality. Using modalityspecific genetic tracing, here we show that ascending mechanosensory and proprioceptive axons, two main types of the DDC afferents, are largely segregated into a medial-lateral pattern in the mouse dorsal column and medulla. In addition, we found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 49 publications
5
119
0
1
Order By: Relevance
“…Immunohistochemistry, in situ hybridization, and image analysis are similar to those previously described (Fleming et al, 2015;Niu et al, 2013;Niu et al, 2014). The detailed experimental procedures are described in the Supplemental Experimental Procedures.…”
Section: Immunohistochemistry In Situ Hybridization and Image Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…Immunohistochemistry, in situ hybridization, and image analysis are similar to those previously described (Fleming et al, 2015;Niu et al, 2013;Niu et al, 2014). The detailed experimental procedures are described in the Supplemental Experimental Procedures.…”
Section: Immunohistochemistry In Situ Hybridization and Image Analysismentioning
confidence: 86%
“…Since many afferent branches were disconnected during slice preparation, and since Aβ fibers from adjacent dorsal roots also innervate the examined spinal level (Brown, 1981;Niu et al, 2013) (Figure 3N), we speculated that 35.2% is an under estimation of Aβ inputs. To test this idea, we generated Vglut1 Cre ; Rosa ChR2(f)/+ ; Ret CFP/+ mice, in which a blue lightactivated cation channel, channelrhodopsin (ChR2) (Boyden et al, 2005), is specifically expressed in all VGLUT1+ neurons, including Aβ fibers ( Figures S4A-F Figures 3J-M).…”
Section: Ret+ Ddh Neurons Receive Excitatory Inputs From Aβ Mechanosementioning
confidence: 99%
“…Using semi-thin sections stained with toluidine blue to visualize axon cross-section profiles within the dorsal column, we found that the volume of the gracile fasciculus, which mainly contains the ascending axons of RA mechanoreceptors (Niu et al, 2013), was greatly reduced in mutant mice compared to controls (Figures 6N-O). Thus, no recovery in axon volume occurs even at later stages.…”
Section: Resultsmentioning
confidence: 99%
“…We previously characterized the functional organization of the DDC pathway (Niu et al, 2013), which contains the ascending axons of Aβ mechanoreceptors and proprioceptors. We showed that ascending axons of Aβ rapidly-adapting (RA) mechanoreceptors and proprioceptors are largely segregated.…”
Section: Introductionmentioning
confidence: 99%
“…La postura de activación es fuente de aferencias sobre el SNC por medio de la información propioceptiva que proporcionan músculos, articulaciones y ligamentos (11,21). Esta postura de activación induce al GCP, activando la respuesta neuronal que producen periódicamente los patrones rítmicos de locomoción (22,23).…”
Section: Resultsunclassified